The Role of Angiotensin Antagonism in Coronary Plaque Regression: Insights from the Glagovian Model. (7th April 2021) - Alkatiri, Abdul H.; Firman, Dony; Alkatiri, Amir A.; Suryajaya, Paskalis I.; Sudharsono, Albert
Abstract : The benefit of antagonizing the effect of the renin angiotensin aldosterone system (RAAS), notably by the use of angiotensin-converting enzyme inhibitor (ACEi) and angiotensin II type 1 receptor blocker (ARB) for coronary artery disease (CAD), has been demonstrated in multiple studies, which may be attributed to their ability to inhibit the deleterious effect of RAAS to the cardiovascular system. It is well known that angiotensin II (Ang II) plays a vital role in atheromatous plaque formation and progression through multiple pathways, including inflammatory and arterial remodeling aspects. Significant coronary atheromatous plaque regression has been previously demonstrated in various studies using statin agents. Similar results have been reported in different studies using angiotensin inhibitor agents, notably ARB agents. Analysis from various trials utilizing ARB showed a significant plaque regression using olmesartan and telmisartan as evaluated by IVUS studies. In contrary, the use of ACEi did not demonstrated significant plaque regression, which may be attributed to the heavy plaque calcification in respective studies. On this review, we aim to present the basic mechanism on the role of RAAS in plaque modulation and its arterial remodeling aspect, which is then integrated with the clinical evidence based on the available intravascular ultrasonography (IVUS) studies on coronary arteries.